Preparing Appropriate Article Type to Publish - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Write-up varies with the type of article; authorship criteria are defined; scientific strength, ethics and institutional approval are important. Journal’s requirement is mandatory and new knowledge is expected from any publication.